Differences in perceptions of medical undergraduates of a military medical school on organizational culture - Bilal Bakir; Mustafa Ozer; Mehmet Cetin; Necmettin Kocak; Turan Fedai; Mesut Cimen (Turkish Society of Public Health Specialists, 2011)
Objective: This study aimed to determine the differences in medical students' perceptions on the organizational culture at a Military Medical School and to reveal possible explanations of them. Method: A total of 205 1st, 2nd, and 6th grade military medical students were invited and 185 of them (coverage rate 90%) participated in the study in 2008. The organizational culture measurement tool previously developed by Turkish researchers was used to determine the perceptions of the students. Reliability analysis, Factor analysis of the scale items and statistical comparisons between groups based on age, grade and certain other characteristics were performed. Results: The average age of participants was 20.2±2.5. The Cronbach's Alpha Value was 0.90 after dropping two items of the original 31-item scale. The symbol dimension of the scale was scored at the lowest level indicating that the symbol is the strongest part of the organizational culture. The scale becomes more reliable when dropping two items, since the Cronbach's Alpha value has been increased from 0.89 to 0.90. The total scale and all its dimensions were stronger among 1st grade students than the older ones. Conclusions: Age, medical education and future concerns of students can be the possible explanations of the given difference. Key Words: Students, Medical, Organizational Culture, Education, Medical, Perception  Bir askeri tıp fakültesi öğrencilerinin örgüt kültürü algılamalarındaki farklılıkları Amaç: Bu çalışma bir askeri tıp fakültesindeki örgüt kültürü ile ilgili olarak tıp fakültesi öğrencilerinin algılamalarındaki farklılıkları belirlemeyi ve bunların muhtemel açıklamalarını ortaya koymayı amaçlamıştır. Yöntem: Toplamı 205 olan 1,2ve 6. sınıf askeri tıp fakültesi öğrencileri 2008 yılı içerisinde çalışmaya davet edilmiş ve 185 öğrenci (katılım oranı %90) çalışmaya katılmıştır. Türk araştırmacılar tarafından daha önce geliştirilmiş olan örgüt kültürü ölçeği öğrencilerin algılamalarını belirlemek üzere kullanılmıştır. Ölçeğin güvenirlik analizleri, faktör analizi ve başta sınıf, yaş olmak üzere belli değişkenlere göre gruplar arası karşılaştırmalar yapılmıştır. Bulgular: Katılımcıların yaş ortalaması 20.2±2.5 dir. Orijinal 31 maddelik ölçekten 2 madde atıldıktan sonra ölçeğin Cronbach Alpha değeri 0.90 olarak bulunmuştur. Ölçeğin sembol boyutu en düşük puanı almıştır ve örgüt kültürünün en kuvvetli öğesi olduğu anlaşılmıştır. Ölçek iki madde atıldıktan sonra Cronbach Alpha değeri 0.89 dan 0.90'a yükseldiğinden daha güçlü hale gelmiştir.Toplam ölçek ve diğer tüm boyutlar birinci sınıf öğrencilerinde diğer öğrencilerden daha kuvvetli bulunmuştur. Sonuç: Yaş, tıp eğitimi ve öğrencilerin gelecek kaygılarının bulunan bu farkın olası açıklamaları olabileceği düşünülmektedir. Anahtar Kelimeler: Öğrenciler, Tıp, Kurum kültürü, Eğitim, Tıbbi, Algı